Quality of Service Gateway Load Balancing Protocol Message Digest algorithm 5 Authentication For Network Quality Enhancement - Sari Dewi; Firmansyah Firmansyah; Rachmat Adi Purnama; Mustofa Mustofa (Universitas Islam Sultan Agung, 2020)
Gateway Load Balancing Protocol (GLBP) Message-Digest algorithm 5 (MD5) is a Cisco's proprietary protocol. GLBP used to enhance the Quality of Service(QoS) on a network. It applies the IP Address Gateway Virtual that redundancy on the local network. GLBP run all used routers in time because of load balancing itself, there is no router used as a standby/backup only. Using the GLBP protocol, all network loads are shared equally to all connected routers. The way the GLBP network works is different from how the HSRP and VRRP networks work, which will run the standby/backup router if the active / master router experiences a problem (failover). The average time needed to redundancy the master to router backup router is 7.6 ms. While the average time needed to change from standby router redundancy to master router redundancy or the master router reused is 33.4 Ms. The average packet loss obtained when the redundancy of the active router change to standby router is 1.7 packet, and The average packet loss obtained when the redundancy of the active router change to standby router is 1.7 packet and 0.5 packets in opposite ways.